Answers

The Brainliest Answer!
2014-10-16T22:21:31+08:00
(x-y+3)² = (x-y+3)(x-y+3)
            = x² - xy + 3x - xy + y² - 3y + 3x - 3y + 9
            = x² + 6x - 2xy - 6y + y² + 9
(x+y-3)² = (x+y-3)(x+y-3)
            = x² + xy - 3x + xy + y² - 3y - 3x - 3y + 9
            = x² - 6x + 2xy - 6y + y² + 9
(x-y-3)² = (x-y-3)(x-y-3)
           = x² - xy - 3x -xy + y² + 3y - 3x + 3y + 9
           = x² - 6x - 2xy + 6y + y² + 9
(x+y+3)² =(x+y+3)(x+y+3)
             = x² + xy + 3x + xy + y² + 3y + 3x + 3y + 9
              = x² + 6x + 2xy + 6y + y² + 9
2 4 2